Bonding Surface Designs in Fixed Orthodontic Attachments - Leila Sadeghalbanaei; Saeed Noorollahian; Zahra Zarei (Hindawi Limited, 2023)
Fixed orthodontic attachments/appliances work as a medium to transfer the force applied to the teeth. In bonded types, several factors affect the attachment bond strength and their clinical success. The primary approach for increasing the bond strength focused on altering the time and concentration of acid etching; however, the results showed that these changes might increase susceptibility to enamel decalcification. The bonding mechanism of orthodontic attachments may be chemical, mechanical, or a combination of both. Most attachment bonding surfaces (ABSs) have no chemical bond to resin composites. Hence, mechanical retention plays a major role. Developing more bonding surfaces by increasing the macroscopic size of the attachments has esthetic and hygienic limitations, so the ABS design plays a more important role in maintaining and improving the bond strength. In this research, different ABS designs are reviewed and categorized according to manufacturing methods and their features.